2010
DOI: 10.4067/s0717-95532010000100010
|View full text |Cite
|
Sign up to set email alerts
|

Identificación Y Análisis De Los Errores De Medicación en Seis Hospitales Brasileños

Abstract: rEsumEnEsta investigación identificó, a través del método de observación directa, los errores de medicación ocurridos en unidades de clínica médica de seis hospitales brasileños. La muestra consistió de las dosis prescritas y administradas en las unidades y observadas durante el periodo de recolección de datos, obedeciendo a un mínimo de 35 dosis/día, durante 30 días. Los resultados evidenciaron los siguientes aspectos: el 1,7% de los medicamentos administrados fue diferente de los prescritos; el 4,8% de las d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
6
0
4
Order By: Relevance
“…Different Latin-American studies have addressed the effect of individual interventions on specific stages of the medication management process [11][12][13][14][15][16]. However, there is no published information on the evaluation of a bundle of preventive measures, applied by a multidisciplinary team to all the stages of medication use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different Latin-American studies have addressed the effect of individual interventions on specific stages of the medication management process [11][12][13][14][15][16]. However, there is no published information on the evaluation of a bundle of preventive measures, applied by a multidisciplinary team to all the stages of medication use.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies conducted in Latin American countries allow the identification of part of the processes and causes most responsible for errors. Those studies have been carried out in hospitalized patients in Brazil [11][12][13], Mexico [14], Uruguay [15], and Argentina [16], reporting ME rates to a specific stage of medication process and different setting than adult ICU. In addition, medical record review has been the method mainly used for detecting MEs [17].…”
Section: Introductionmentioning
confidence: 99%
“…These findings demonstrate the wide variability of prescription rates in private vs public Mexican hospitals. In other countries with similar healthcare conditions to Latin America, one Brazilian study found a ME rate of 7.4% and Colombian study found a ME rate of 97.3% [36] with a follow-up publication estimating that 67.2% of these errors reach the patient [37,38]. The importance of this study demonstrates the need to include trained pharmacists to the healthcare team in Mexican public hospitals; to validate prescriptions, to provide prescription training to health care providers, and most importantly, to enhance drug safety.…”
Section: Discussionmentioning
confidence: 97%
“…These findings demonstrate the wide variability of prescription rates in private vs public Mexican hospitals. In other countries with similar healthcare conditions to Latin America, one Brazilian study found a ME rate of 7.4% and Colombian study found a ME rate of 97.3% [ 36 ] with a follow-up publication estimating that 67.2% of these errors reach the patient [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Con la revisión de la literatura, se identificó que existe una limitada evidencia que soporte los conocimientos y usos de medicamentos en vías y condiciones no establecidos en la ficha técnica; por tanto, no existe una definición clara y se presenta un desconocimiento en los profesionales de la salud (10,(13)(14)(15)17). Otras características comunes sobre los resultados de las investigaciones son: el uso fuera de etiqueta de forma común entre los pediatras, dado que existe falta de medicamentos específicamente diseñados y comercializados para niños de diferentes grupos de edad (13-17); información ausente o reducida para la correcta utilización de los medicamen-tos; alto riesgo de errores y eventos relacionados con los medicamentos (11,12,14,17).…”
Section: Fuente: Autoraunclassified